Corporate Social Responsibility, Corporate Governance, and Corporate Financial Performance - Juniati Gunawan; Devica Pratiwi (Indonesian Management and Accounting Research, 2017)
This paper aims to analyze the influence of corporate social responsibility disclosures (CSRD) by corporate governance (CG) as a moderating variable on corporate financial performance (CFP). The CSRD were measured by the United Nations Environment Programme (UNEP) items and CG practices were evaluated by the Corporate Governance Perception Index (CGPI). The sample of 108 annual reports from 2011 to 2014, which were listed in the ‘Indonesia Most Trusted Companies Awards’ were analyzed through 2012 to 2015 SWA magazine. The moderated regression test was applied to analyze the corporate social responsibility disclosure (CSRD) to CFP, moderated by CG. The CFP were proxied by return on assets (ROA) and return on equity (ROE). This study reveals that CSRD has a significant positive influence to the company's ROA and ROE, and CG has been found weakening the relation between CSRD in influencing the ROA and ROE.